ANALISIS KORELASI AKTIVITAS MASYARAKAT PERKOTAAN PENGGUNA KENDARAAN BERMOTOR DENGAN JUMLAH SEL DARAH MERAH YANG MENGALAMI HEMOLISIS - Novianti, Titta (Indonesian Journal of Nursing Health Science, 2016)
AbstractAir, water and soil pollution is getting higher than before and getting the thresholds that are harmful to human health. Various types of metal is now widely polluting our environment, including metal lead potentially harmful to human health. Metal Lead (Pb) is a metal that are pollutants derived from motor vehicle fuel and industrial activities. Nearly 85% of lead contamination in humans takes place through the respiratory, digestive and 14% through the remainder through the skin. Children are more easily exposed to lead than in adults. In children, lead impact on the level of intelligence, growth and hearing disorders, causes anemia and can cause attention deficit disorder and conduct disorder. As many as 30-40% of lead will be absorbed into the blood stream and 95% bound to erythrocytes. Lead is a metal substance that can poison the environment and affect the health of the human body because it can spread to the entire system in the body. Substance metallic lead coined the potential damage the protein hemoglobin in red blood cells, which causes red blood cell hemolysis. The ability of a very high chemical affinity of heavy metal elements of the hemoglobin causes heavy metals bond with hemoglobin is much easier than with oxygen. As a result, the metabolism of the cells disrupted and can cause death. Lead can also affect the activity of enzimi that play a role in the process of formation of hemoglobin (Hb) in red blood cells. Given the very dangerous metallic lead on human health because it affects the damage of cells and tissues including red blood cells, it is important to do research on how the effect of metallic lead directly on human blood samples against damage and a decrease in the number of red blood cells. Research done simply by looking at the morphology of red blood cells and the number of red blood cells which undergo hemolysis blood of 10 people masyarakarat urban population is thought to have exposed lead pollutants that cause red blood cell hemolysis. Used negative control blood samples of 10 people suspected of rural population has not been exposed to lead pollutants. Before sampling, given a questionnaire to ascertain whether the possibility of exposure to lead pollutants. Each sample was observed morphology of red blood cells as well as the count of the number of red blood cells that undergo hemolysis. Comparison test conducted two groups by using Man Whitney test, as would be obtained numerical data, non-parametric, two pairs were unrelated groups, to see whether there is any difference in the number of red blood cells that undergo hemolysis resulting from exposure to pollutants lead between the two groups.Keywords: Pollutants, Lead, red blood cells, hemolysis